Pendidikan Islam Berwawasan Lingkungan Berbasis Pondok Pesantren - Al Hamid, S. Ahmad (Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan Jawa Timur, 2024)
Islamic education with an environmental perspective based on Islamic boarding schools is important to promote. Islamic boarding schools that use a full day education system are closely related to the need for a healthy environment, not only Islamic boarding schools but society in general also needs the same thing. This study uses the Resecah Library method with data analysis using content analysis. This study concludes that environmentally conscious Islamic education in Islamic boarding schools begins with two things, first, strengthening the values ​​of the faith which has a paradigm of caring for the environment and secondly applying the environmental paradigm in everyday life.